Control sites in the sequence at the beginning of T7 gene 1. - McConnell, D J (1979)
The DNA sequence of the fragment Hind.30, 378 bases long, from the beginning of gene 1 of T7 is presented. It contains the C promoter, two in vitro transcriptional terminator sites and a sequence of 171 bases which probably codes for the N terminus of the T7 RNA polymerase. The sequence also codes for the RNase III cleavage site before gene 1. The overlaps with the transcriptional terminators, The RNA transcript of the sequence about the terminators can be arranged in a set of alternative double-stranded hairpin structures. It is suggested that conversion between these structures may have a role in termination; this may be influenced by interactions with ribosomes and RNase III. The region of the C promoter between genes 0.7 and 1 thus contains several sites which may be involved in the control of transcription and translation.